Artificial insemination in Moroccan sheep: present and perspectives - El Amiri B.; Druart X. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Despite the large number and the importance of sheep in Morocco, artificial insemination (AI) in this species is not yet an operative tool for the ovine breeding development and selection. In the actual context of climatic change, many countries consider AI as a major tool for the genetic improvement and the selection of specific traits of interest for sustainable development. In fact, the first trials in Morocco started in 1987 and have continued at a very slow pace until 2000. Recently, an integrated study has been carried out in a collaborative approach merging INRA-Settat-Morocco and INRA-Nouzilly-France. The present work aims at highlighting the findings resulting from this collaboration. Two cycles of three years each have been set up. The Studies concerned the characterization of males and females reproductive features (hormonal profiles, estrus synchronization protocols, seasonal variations of semen production and quality, semen conservation, effects of different diluents, exo-cervical AI trials). However the results obtained in the present study could not alone promote the technique. The currently biggest and most urgent challenge for the country is to gather all national and international experts, take into account the experience of our Mediterranean neighbors in order to advance the AI activity in sheep and not to forget involving the producers at every step.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)